Conselho de Classe: possibilidades de atuação na formação de docentes da EPTNM do IFRO-Campus Ji-Paraná - Andrade, Josefa Aparecida Pereira de (2019)
This research aimed to investigate in which aspects the Class Council can act in the training of teachers of the Technical Professional Education of Medium Level. To achieve this goal, the relationship between the Class Council and teacher training was established, and later, based on the collaborative work developed between the researcher and the research participants, to carry out the planning, implementation and evaluation of the formative actions. It is a research of qualitative approach that used as a methodological strategy the collaborative research, organized in four phases: diagnosis, planning, implementation and evaluation. These phases were performed in two moments: in the first, called light beam, the diagnostic phase occurred; in the second, called coproduction and training, the planning, implementation and evaluation phases. The participants of the research were organized in two groups: from the first group participed forty (40) students from the integrated technical courses (Forestry Technician, Chemistry Technician and Computer Technician), three professionals from the Technical-Pedagogical Team and forty and three (43) teachers, teachers of integrated technical courses; of the second group participated six (6) professors, professors at IFRO, who gave origin to the Collaborative Group. As techniques and instruments of data production, we made use, respectively, of talk wheel, formative moment, study moment, collaborative observation and documentary analysis; questionnaires, audio recording and field diary. For the accomplishment of the analysis of the data, it was adopted the ATD (Discursive Textual Analysis). The results show that the Class Council based on the processes of evaluation, self-assessment and reflection can influence the training of teachers of the EPTNM, in the following aspects: promote the integration of knowledge, the didactic-pedagogical updating of teachers and the diagnosis of their training needs. These results allowed the construction of the educational product, a proposal for the Formative Class Council with the objective of collaborating with the (re)configuration of the Class Council in the field of Professional Technical Education at the Middle Level, based on participation, reflection and evaluation/self-evalution of students, teachers and professionals of the Technical-Pedagogical Team.